Language engineering for the Semantic Web: a digital library for endangered languages. Endangered languages, Ontology, Digital library, Multimedia, EMELD, Intelligent querying and retrieval, ImageSpace - Lu Shiyong; Liu Dapeng (Information Research: An International Electronic Journal)
In this paper, we describe the effort undertaken at Wayne State University to preserve endangered languages using the state-of-the-art information technologies. In particular, we discuss the issues involved in such an effort, and present the architecture of a distributed digital library for endangered languages which will contain various data of endangered languages in the forms of text, image, video, audio and include advanced tools for intelligent cataloguing, indexing, searching and browsing information on languages and language analysis. We use various Semantic Web technologies such as XML, OLAC, ontologies so that our digital library becomes a useful linguistic resource on the Semantic Web.